2008
DOI: 10.1016/j.jalz.2008.05.1855
|View full text |Cite
|
Sign up to set email alerts
|

P3‐287: TDP‐43 A315T mutation in familial motor neuron disease

Abstract: To identify novel causes of familial neurodegenerative diseases, we extended our previous studies of TAR DNA‐binding protein 43 (TDP‐43) proteinopathies to investigate TDP‐43 as a candidate gene in familial cases of motor neuron disease. Sequencing of the TDP‐43 gene led to the identification of a novel missense mutation, Ala‐315‐Thr, which segregates with all affected members of an autosomal dominant motor neuron disease family. The mutation was not found in 1,505 healthy control subjects. The discovery of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
227
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(235 citation statements)
references
References 0 publications
8
227
0
Order By: Relevance
“…It is well established that TDP-43 proteinopathies contribute to the pathological progression of motor-neuron diseases; [12][13][14][15][16][17] however, the interaction between virus infection and the host TDP-43 pathway has not yet been explored. In this study, we first examined the protein expression of TDP-43 in various models of CVB3 infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that TDP-43 proteinopathies contribute to the pathological progression of motor-neuron diseases; [12][13][14][15][16][17] however, the interaction between virus infection and the host TDP-43 pathway has not yet been explored. In this study, we first examined the protein expression of TDP-43 in various models of CVB3 infection.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Previous studies have shown that mutations of TDP-43 are linked with neurodegenerative diseases, in particular, amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). [12][13][14][15][16][17] In addition, aberrant cleavage and cytoplasmic aggregation of TDP-43 are identified as molecular signatures for most forms of ALS and FTLD and contribute significantly to disease progression. 18 However, the role of TDP-43 in virus-induced diseases has not been studied.…”
mentioning
confidence: 99%
“…This could be due to reduced penetrance of p.G357R, which is in agreement with other reported TARDBP mutations. [8][9][10][11][12]18 …”
Section: Discussionmentioning
confidence: 99%
“…This is within the range of what has been estimated in other ALS populations, 1-3%. [8][9][10][11][16][17][18][19] However, the ALS patients in our study were intentionally selected for a positive family history suggesting that mutations in TARDBP are rare in the Nordic ALS population.…”
Section: Novel Tardbp Mutations H-h Chiang Et Almentioning
confidence: 99%
See 1 more Smart Citation